Residual surface stress: comparing traditional and modulated tool path machining processes. Issue 14 (21st September 2016) - Schmidt, P.; Handy, R.; Anderson, T.; Rees, T.; Morrell, J.; Williams, W.; Jackson, M.
Abstract : Traditional machining processes, where material is removed by a cutting tool from a workpiece, can introduce residual stresses at the surface of machined pieces. This paper provides an examination of an alternative machining methodology called modulated tool path machining. The ultimate objective of this research is to determine the effects of modulated tooling path machining processes, as applied to control chip geometry, on the surface stress of selected materials. Residual stresses in machined samples were characterised through the use of X-ray diffraction by comparing the modulated path method with a more traditional material removal technique (i.e. constant surface speed and constant contact). This paper is part of a Themed Issue on Measurement, modelling and mitigation of residual stress.